Tele-stroke Services in Areas of Rural Nepal: A Dire Need - Ghimire, Sagun (Journal of Karnali Academy of Health Sciences, 2023)
With the increasing burden of non-communicable diseases in South Asian countries, Nepal also holds a pertinent position with the rapidly increasing prevalence of non-communicable diseases. Among the South Asian countries with the least developed health infrastructure in Nepal, the hurdles of providing equal health services to all demographic and geographic groups of people had always been a matter of serious concern. Moreover, the citizens of rural Nepal had always been kept at a distance from even minor to several major healthcare services for decades and stroke-related illness falls under one of those major diseases with spiking rates of hypertension and diabetes mellitus. Traditional risk factors, lifestyle and feeding practices of those regions combined with arduous transportation facilities barring the rural citizens from getting health care services from tertiary care centers have increased morbidity rates as well. Along with it the numbers of neurologists and stroke centers providing specialist services are not in par with the burden of stroke-related illness. Adding to it such stroke care services are below scarce level and completely devoid in most of the areas of rural Nepal which is a matter of global health concern. Telestroke service if properly implemented can act a modern solution to provide access to such special health care services preventing rural citizens from lifelong disability and dependence.